Cerebral embolization, silent cerebral infarction and neurocognitive decline after thoracic endovascular aortic repair. Issue 4 (12th February 2018) - Perera, A. H.; Rudarakanchana, N.; Monzon, L.; Bicknell, C. D.; Modarai, B.; Kirmi, O.; Athanasiou, T.; Hamady, M.; Gibbs, R. G.
Abstract: Background: Silent cerebral infarction is brain injury detected incidentally on imaging; it can be associated with cognitive decline and future stroke. This study investigated cerebral embolization, silent cerebral infarction and neurocognitive decline following thoracic endovascular aortic repair (TEVAR). Methods: Patients undergoing elective or emergency TEVAR at Imperial College Healthcare NHS Trust and Guy's and St Thomas' NHS Foundation Trust between January 2012 and April 2015 were recruited. Aortic atheroma graded from 1 (normal) to 5 (mobile atheroma) was evaluated by preoperative CT. Patients underwent intraoperative transcranial Doppler imaging (TCD), preoperative and postoperative cerebral MRI, and neurocognitive assessment. Results: Fifty-two patients underwent TEVAR. Higher rates of TCD-detected embolization were observed with greater aortic atheroma (median 207 for grade 4–5 versus 100 for grade 1–3; P = 0·042), more proximal landing zones (median 450 for zone 0–1 versus 72 for zone 3–4; P = 0·001), and during stent-graft deployment and contrast injection ( P = 0·001). In univariable analysis, left subclavian artery bypass (β coefficient 0·423, s.e. 132·62, P = 0·005), proximal landing zone 0–1 (β coefficient 0·504, s.e. 170·57, P = 0·001) and arch hybrid procedure (β coefficient 0·514, s.e. 182·96, P < 0·001) were predictors of cerebral emboli. Cerebral infarction was detected in 25 of 31 patients (81 per cent) who underwent MRI: 21 (68 per cent) silent and four (13 per cent) clinical strokes. Neurocognitive decline was seen in six of seven domains assessed in 15 patients with silent cerebral infarction, with age a significant predictor of decline. Conclusion: This study demonstrates a high rate of cerebral embolization and neurocognitive decline affecting patients following TEVAR. Brain injury after TEVAR is more common than previously recognized, with cerebral infarction in more than 80 per cent of patients.